2015
DOI: 10.3233/jrs-150665
|View full text |Cite
|
Sign up to set email alerts
|

Evidence-based information leads to reduction in inappropriate drug prescribing: Results from Indian older inpatients

Abstract: The findings of this study provide evidence that provision of unbiased evidenced based information is the best possible means for improvement of pharmacotherapy in older patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 13 publications
0
12
1
Order By: Relevance
“…Polypharmacy is one of the risk factor for PIM use and adverse drug events. 24,25 Prevalence of PIM use among hospitalized older adults in the present study was found to be 32.14% which is higher than that reported in some prospective studies in India by Zaveri HG et al 23 (23.5%), Harugeri A et al 24 (23.5%), Kashyap M et al 26 (21%), Shah KN et al 27 (29.3%), Pradhan S et al 28 (21.86%) and Vishwas HN et al 29 (24.6%). While some prospective studies showed higher prevalence of PIM use [Danisha P et al 30 (53%) and Momin TG et al 31…”
Section: Discussioncontrasting
confidence: 48%
See 1 more Smart Citation
“…Polypharmacy is one of the risk factor for PIM use and adverse drug events. 24,25 Prevalence of PIM use among hospitalized older adults in the present study was found to be 32.14% which is higher than that reported in some prospective studies in India by Zaveri HG et al 23 (23.5%), Harugeri A et al 24 (23.5%), Kashyap M et al 26 (21%), Shah KN et al 27 (29.3%), Pradhan S et al 28 (21.86%) and Vishwas HN et al 29 (24.6%). While some prospective studies showed higher prevalence of PIM use [Danisha P et al 30 (53%) and Momin TG et al 31…”
Section: Discussioncontrasting
confidence: 48%
“…Beers criteria states it as inappropriate drug in older adults as there is increased risk of CNS effects, bradycardia and orthostatic hypotension. 20 Benzodiazepines had been reported as most commonly used PIMs in several studies, 26,27,30,32 as Beers criteria states that benzodiazepines increase the risk of cognitive impairment, delirium, falls and fractures in older adults. 20 A total of 31 ADRs in 30 (26.7%) patients were observed in present study which was higher than reported by Danisha P et al 30 (5%), Onda M et al 33 (8%) and Pasina L et al 34 (9.7%).…”
Section: (40%)]mentioning
confidence: 99%
“…After removing 165 duplicates, a total of 1835 titles and abstracts were screened to determine if they met the inclusion criteria, as described in the methodology section. Full-text assessment of 119 potentially relevant articles resulted in 27 eligible studies (Bhatt et al, 2019;Chandrasekhar et al, 2019;Motallebzadeh et al, 2019;Pradhan and Panda, 2018;Benjamin et al, 2018;Devarapalli et al, 2017;Kumar et al, 2017;Pradhan et al, 2017;Narvekar et al, 2017;Borah et al, 2017;Rakesh et al, 2017;Anjum et al, 2017;Swathi and Bhavika, 2016;Salwe et al, 2016;Chowta et al, 2016;Kashyap et al, 2015;Danisha et al, 2015;Umar et al, 2015;Undela et al, 2014;Dhikav et al, 2014;Karandikar et al, 2013;Momin et al, 2013;Nagendra et al, 2012;Shah et al, 2011;Mandavi et al, 2011;Zaveri et al, 2010;Harugeri et al, 2010), as shown in Figure 1. The list of articles that are excluded (n 92) due to various reasons is presented in Supplementary Table S2.…”
Section: Study Selectionmentioning
confidence: 99%
“…Studies from West India (51%, 95% CI: 44-58), and North-east India reported higher prevalence of polypharmacy (72%, 95% CI: 65-79). Moreover, the majority of studies were conducted in South India (Harugeri et al, 2010;Nagendra et al, 2012;Kashyap et al, 2015;Umar et al, 2015;Chowta et al, 2016;Salwe et al, 2016;Swathi and Bhavika, 2016;Devarapalli et al, 2017;Narvekar et al, 2017;Pradhan and Panda, 2018;Bhatt et al, 2019;Chandrasekhar et al, 2019;Motallebzadeh et al, 2019), where the prevalence of polypharmacy was 49% (95% CI: 42-57; I 2 95.3%, p < 0.01). The data on the prevalence of polypharmacy in other regions is summarized in Figure 2.…”
Section: Prevalence Of Polypharmacymentioning
confidence: 99%
See 1 more Smart Citation